Karakteristik Corak Penafsiran Al-Qur’an dalam Surat Al-Fatihah Perspektif Tafsir Al-Azhar dan Tafsir Al-Misbah - Faisal, Muhammad (JURNAL AT-TURAS, 2022)
This article describes a model for the discovery of the Qur'an which is applied by Indonesian commentators, namely Tafsir al-Misbah by Quraish Shihab and Tafsir al-Azhar by HAMKA, both of which are phenomenal book of tafseer written by Indonesian scholars. The focus of the study is the pattern of findings applied by Quraish Shihab and HAMKA to the letter al-Fatihah in the two commentaries. This research is a literature study type and uses a descriptive-qualitative approach and applies a comparative method. The data obtained in this study comes from two categories, namely primary and secondary data, the primary data is the book of interpretation of al-Misbah by Quraish Shihab and Tafsir al-Azhar by HAMKA, while secondary data comes from articles, papers, books, and so on. The author concludes that the disclosure of al-Fatihah Quraish Shihab has a pattern of interpretation that is generally almost the same as that imagined by HAMKA, namely the pattern of language and fiqh. However, if seen specifically there seems to be a slight difference regarding the pattern, where Quraish Shihab dominates his linguistic pattern in translating of surah al-Fatihah, while HAMKA dominates the fiqh pattern. This can be seen from the existence of sub-chapters that were made specifically when the surah al-Fatihah was obscured. For example, the linguistic pattern in al-Misbah's interpretation have a sub-chapter "The meaning of ba read bi in bismillah", in this sub-chapter Quraish Shihab tries to explain surah al-Fatihah in bismillah sentences in language. Meanwhile, his pattern of fiqh in can be seen in the interpretation of al-Azhar in surah al-Fatihah by writing a sub-chapter namely "Al-Fatihah as the pillars of prayer". Where in this sub-chapter HAMKA tries to explain how to read surah al-Fatihah from a legal perspective.